2010
DOI: 10.3109/08039488.2010.531762
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of buprenorphine maintenance treatment as compared to a syringe exchange program among buprenorphine misusing opioid-dependent patients

Abstract: BMT appears to be an effective treatment for opioid dependents using mainly buprenorphine intravenously. On the other hand, bare SEP appears to result in high drop-out, not significant improvements and deaths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 17 publications
0
15
0
1
Order By: Relevance
“…Lifetime prevalence of illicit methadone use among intravenous drug users outside treatment has varied between 17% and 95% in different studies, but high prevalence is the rule rather than the exception (Davis & Johnson, 2007;Hall, Leukefeld, & Havens, 2013;Roche, McCabe, & Smyth, 2008;Vlahov et al, 2007). Illicit buprenorphine use is prevalent, as well (Håkansson, Medvedeo, Andersson, & Berglund, 2007;Yokell, Zaller, Green, & Rich, 2011) and in some countries this substance has become the most common opioid on the illicit market (Aalto, Visapää, Halme, Fabritius, & Salaspuro, 2011;Moatti, Vlahov, Feroini, Perri, & Odabia, 2001;Yokell et al, 2011). Methadone and buprenorphine typically enter a user's drug career at a late stage, and they are rare among younger people, unless they have already developed severe drug problems (Richert & Johnson, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Lifetime prevalence of illicit methadone use among intravenous drug users outside treatment has varied between 17% and 95% in different studies, but high prevalence is the rule rather than the exception (Davis & Johnson, 2007;Hall, Leukefeld, & Havens, 2013;Roche, McCabe, & Smyth, 2008;Vlahov et al, 2007). Illicit buprenorphine use is prevalent, as well (Håkansson, Medvedeo, Andersson, & Berglund, 2007;Yokell, Zaller, Green, & Rich, 2011) and in some countries this substance has become the most common opioid on the illicit market (Aalto, Visapää, Halme, Fabritius, & Salaspuro, 2011;Moatti, Vlahov, Feroini, Perri, & Odabia, 2001;Yokell et al, 2011). Methadone and buprenorphine typically enter a user's drug career at a late stage, and they are rare among younger people, unless they have already developed severe drug problems (Richert & Johnson, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] Illicit buprenorphine use is prevalent, as well, [16][17] and in some countries this substance has become the most common opioid on the illicit market. [17][18][19] Methadone and buprenorphine typically enter a user's drug career at a late stage, and they are rare among younger people, unless they have already developed severe drug problems. 20 The substances are mainly used by people with a long-standing opioid addiction.…”
Section: Introductionmentioning
confidence: 99%
“…However both medications were well accepted by buprenorphine injectors and outcomes on both were significantly better than if treated only with clonidine. In Finland, a naturalistic follow-up study found an 83% retention rate in opioid dependent patients that were injecting buprenorphine and treated with sublingual buprenorphine (Aalto et al, 2011). …”
Section: Introductionmentioning
confidence: 99%